Removal of active dyes by ultrafiltration membrane pre-deposited with a PSFM coagulant: Performance and mechanism. (May 2019) - Tang, Lipeng; Xiao, Feng; Wei, Qunshan; Liu, Yanbiao; Zou, Yubin; Liu, Jianshe; Sand, Wolfgang; Chow, Christopher
Abstract: A new, environmental friendly, polysilicate ferric manganese (PSFM) coagulant, composed of Fe, Mn and Si, was designed and developed. As part of the process, the PSFM flocs were then deposited onto an ultrafiltration (UF) membrane to increase the removal of active dyes and its antifouling properties in the presence of the active dye was tested. Influencing factors, such as dosage of coagulant and solution pH, were systematically investigated and included as the process optimization. The results show that PSFM flocs were well distributed on the membrane surface and a dense and homogeneous deposition layer was formed under optimal conditions. According to the characterization of PSFM floc by Fourier infrared (FTIR) and X-ray photoelectron spectroscopy (XPS), the major phase of PSFM floc is determined to be Mnx Fey Siz Ow (OH)i and the functional groups of this component contribute positively to the coagulation performance. The removal rate of the active yellow dye reached 86% at pH 5.0 with small and regular floc formed in the dense deposition layers. At pH 11.0 loose deposition layers were formed by large flocs and the removal of the active yellow dye reduce to 11%. Therefore, PSFM has a commendable potential to be used for producing a kind of deposited UF membrane with an excellent performance by controlling the forms of flocs and the deposition layers, which is the key mechanism to achieve a high efficiency for removal of active yellow dye. Graphical abstract: Image 108146 Highlights: UF membrane with pre-deposited PSFM flocs has been preliminarily established. UF membrane with pre-deposited PSFM flocs achieves high removal for active dye. Pre-deposited PSFM flocs could alleviate membrane fouling. PSFM may be a good option as inline coagulation-membrane filtration process.